'Not there': 'dark matter' in Samuel Beckett's Footfalls. Issue 3 (2nd September 2021) - Little, James
ABSTRACT: Samuel Beckett's 1976 play Footfalls is built around elements which are invisible, or not quite there, in performance. This article uses the concept of 'dark matter' to analyse the play's theatrical absences and their construction in the creative process. An analysis of the play's manuscripts, digitized and transcribed as part of the Beckett Digital Manuscript Project, reveals that such 'dark matter' is not just a feature of the published text or performance, but is constitutive of Beckett's creative process, particularly with regard to how he stages the mind. This article studies the models of mind staged in Footfalls in order to argue that Beckett uses the play's 'dark matter' to enact the breakdown of subject and object in the play.